High ANO1 expression is a prognostic factor and correlated with an immunosuppressive tumor microenvironment in pancreatic cancer - Zhang, Guangnian; Shu, Zhihui; Yu, Jun; Li, Jianshui; Yi, Pengsheng; Wu, Bin; Deng, Dawei; Yan, Shu; Li, Yong; Ren, Dongmei; Hou, Yifu; Lan, Chuan (Frontiers in Immunology, 2024)
Background: Aminooctylamine (ANO1) plays an oncogenic role in various cancers. However. its role in pancreatic cancer (PC) has rarely been studied. This study investigated the prognostic value of ANO1 and its correlation with the tumor microenvironment (TME) in PC.Consecutive patients with PC (n = 119) were enrolled. The expression of ANO1 in cancer cells, the expression of fibroblast activation protein (FAP) and alpha smooth muscle actin in cancerassociated fibroblasts (CAFs), and the numbers of CD8-and FOXP3-positive tumor-infiltrating lymphocytes (TILs) were evaluated using immunohistochemistry. The prognostic value of ANO1 and its correlation with CAF subgroups and TILs were analyzed. The possible mechanism of ANO1 in the TME of PC was predicted using the the Cancer Genome Atlas (TCGA) dataset.The expression of AN01 was correlated with overall survival (OS) and disease-free survival.Multi-factor analysis showed that high ANO1 expression was an independent adverse prognostic factor for OS (hazard ratio, 4.137; P = 0.001). ANO1 expression was positively correlated with the expression of FAP in CAFs (P < 0.001) and negatively correlated with the number of CD8-positive TILs (P = 0.005), which was also validated by bioinformatics analysis in the TCGA dataset.Moreover, bioinformatic analysis of the TCGA dataset revealed that ANO1 may induce an immunosuppressive tumor microenvironment in pancreatic cancer in a paracrine manner.ANO1 is a prognostic factor in patients with PC after radical resection. ANO1 may induce an immunosuppressive tumor microenvironment in PC in a paracrine manner, suggesting that ANO1 may be a novel therapeutic target.